Furan derivatives from Lannea kerstingii. (June 2017) - Tameko, Joseph Eric Mbasso; Chouna, Jean Rodolphe; Nkeng-Efouet-Alango, Pépin; Tapondjou, Leon Azefack; Sewald, Norbert
Graphical abstract: Highlights: MeOH extract of the stem bark of Lannea kerstingii was investigated. Two previously undescribed furane derivatives, lannefuran A (1 ) and lannefuran B (2 ). Lannefuran A (1 ) exhibited very low antiplasmodial activity against Plasmodium falciparum 3D7. Abstract: Two new furan derivatives, lannefuran A (1 ) and lannefuran B (2 ) were isolated from the stem bark extract of Lannea kerstingii Engl. & K. Krause together with five known compounds, namely: taraxerol, stigmast-4-en-3-one, monoglyceride of hexacosanoic acid, β -sitosterol and its glucoside. Their structures were determined by means of 1D and 2D NMR, IR, and HR–EI–MS spectra and comparison with the data of known analogues reported in the literature. Lannefuran A (1 ) exhibited very low antiplasmodial activity against Plasmodium falciparum 3D7.